PENERAPAN SOFTWARE ANALISIS STRUKTUR UNTUK MEMBANTU PEMAHAMAN DALAM MEMPELAJARI MATA KULIAH MEKANIKA TEKNIK DI S1 PENDIDIKAN TEKNIK BANGUNAN - Pradya Arhain Darlestio (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
Learning the Mechanics Engineering course at the undergraduate level of Building Engineering Education requires a profound understanding of the basic concepts of structure and the forces at work within structural systems. However, students often encounter difficulties in visualizing and analyzing structures comprehensively. This research introduces a novel approach utilizing structural analysis software such as Robot Structure, SAP2000, and ETABS to enhance students' understanding of mechanical engineering. By involving the application of the latest structural analysis software in teaching, it enables students to interactively manipulate structural models and observe the eflects of various forces and loads. This article delineates the implementation of this approach within the curriculum of the Mechanics Engineering course and evaluates its impact on students' understanding and performance. The results indicate a significant improvement in students' understanding of structural concepts and analytical abilities, as well as an increase in their interest and motivation in learning. This research provides valuable insights into the potential use of technology to enhance the eflectiveness of learning in the field of civil engineering.